2022
DOI: 10.3390/jof8080845
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Phenotype, and Molecular Identification of Clinical and Environmental Fusarium solani Species Complex Isolates from Malaysia

Abstract: Fusarium infections in humans (fusariosis) and in economically important plants involve species of several Fusarium species complexes. Species of the Fusarium solani species complex (FSSC) are the most frequent cause of human fusariosis. The FSSC comprises more than 60 closely related species that can be separated into three major clades by multi-locus sequence typing (MLST) using translation elongation factor 1-alpha (TEF1-α) and RNA polymerase II (RPB2) DNA sequences. The MLST nomenclature for clade 3 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…A phylogenetic tree of the F. solani species complex is shown in Figure 3 . Our phylogenetic tree was constructed with the aim of being similar to those in previous phylogenetic studies [ 50 , 55 , 56 ]. The phylogenetic tree successfully assigned the two fungal isolates (SDBR-CMU463 and SDBR-CMU464) assessed in this investigation within the same clade of F. paranaense , which consisted of the type species CML 1830.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phylogenetic tree of the F. solani species complex is shown in Figure 3 . Our phylogenetic tree was constructed with the aim of being similar to those in previous phylogenetic studies [ 50 , 55 , 56 ]. The phylogenetic tree successfully assigned the two fungal isolates (SDBR-CMU463 and SDBR-CMU464) assessed in this investigation within the same clade of F. paranaense , which consisted of the type species CML 1830.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, two isolates of F. compactum (SDBR-CMU461 and SDBR-CMU462) and two isolates of F. paranaense (SDBR-CMU463 and SDBR-CMU464) were isolated from fruit rot lesions on watermelons from northern Thailand. These four fungal isolates were identified using a combination of their morphological features and phylogenetic analysis of multiple genes, according to the identification techniques used in previous studies [ 35 , 36 , 37 , 38 , 50 , 55 , 56 ]. Prior to this study, F. compactum and F. paranaense had previously been identified as plant pathogens; for example, F. compactum was found to be the cause of leaf spot on sweet cherry ( Prunus avium L.) [ 69 ] and leaf blight on maize ( Zea mays L.) [ 70 ] in China, root rot of banana ( Musa sp.)…”
Section: Discussionmentioning
confidence: 99%
“…Non-negligible differences in species identification by morphology and molecular phylogenetics have been reported in other recent studies, illustrating the need to integrate both morphological characteristics and molecular technologies in the identification of Fusarium spp. [98,99].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of our study, the TEF1 and RPB2 sequences proved to be sufficient for the unambiguous assignment of the nineteen isolates to four Fusarium species. Many recent studies have used the same two regions for Fusarium species identification [ 7 , 8 , 38 , 39 , 40 , 41 , 42 , 43 ]. Our research has confirmed that sequencing is essential for distinguishing Fusarium species.…”
Section: Discussionmentioning
confidence: 99%